Evaluation and Monitoring of Mycobacterium leprae Transmission in Household Contacts of Patients with Hansen's Disease in Colombia. - Marcela Romero-Montoya; Juan Camilo Beltran-Alzate; Nora Cardona-Castro (Public Library of Science (PLoS), 2017)
Leprosy in Colombia is in a stage of post elimination-since 1997, prevalence of the disease is less than 1/10000. However, the incidence of leprosy has remained stable, with 400-500 new cases reported annually, with MB leprosy representing 70% of these case and 10% having grade 2 disability. Thus, leprosy transmission is still occurring, and household contacts (HHCs) of leprosy patients are a population at high risk of contracting and suffering from the effects of the disease during their lifetime. We performed a cross-sectional study with the aim of evaluating leprosy transmission within Family Groups (FGs) from four Colombian departments: Antioquia, Bolívar, Córdoba and Sucre. This study included 159 FGs formed by 543 HHCs; 45 FGs were monitored twice, first in 2003 and again in 2012. Migration, forced displacement by violence, loss of contact with the health center and the lack of an agreement to participate in the second monitoring were the primary reasons not all FGs were tested a second time. In each HHC, a clinical examination was performed, epidemiological data recorded, the bacillary index determined, DNA was isolated for M. leprae detection by nested PCR and IgM anti-phenolic glycolipid-I (PGL-I) titers were inspected. Further, DNA from M. leprae isolates were typed and compared among FGs. Twenty-two (4.1%) of the 543 HHCs had IgM anti-PGL-I positive antibody titers, indicating infection. Nasal swabs (NS) taken from 113 HHCs were tested by RLEP PCR; 18 (16%) were positive for M. leprae DNA and two new leprosy cases were detected among the HHCs. Of the confirmed HHCs with leprosy, it was possible to genotype the bacterial strains from both the index case and their HHCs. We found that the genotype of these two strains agreed at 9 markers, showing the individuals to be infected by the same strain, indicating familiar transmission. HHCs of leprosy patients not only are a high-risk population for M. leprae infection, they can act as M. leprae carriers and therefore serve as sources for transmission and infection. Our results confirm familiar leprosy transmission and suggest that follow-up of HHCs is a good strategy for early diagnosis of leprosy and to monitor its transmission.